The Effects of Hymeniacidon sp. Sponge Extract to The Level of Parasitemia Trypanosoma evansi in BALB/c Mice (Mus musculus L.) - Maya Ekaningtias (Jurnal Sain Veteriner, 2014)
Trypanosoma evansi is a blood protozoa which has infected many livestock like cow, horse, and buffalo and caused disease so called surra. Disease medication of surra depends on the latest invention of trypanocidal medicine, but must of synthetic medicine has become resistance. Therefore, another alternative has been developed using natural materials. Sponge is a kind of oceanic organism which well known for producing secondary metabolite which has biology activity. One of them is Hymeniacidon sp. which known containingterpenoid bioactive compound. The purpose of this research is to study the effect of Hymeniacidon sp. sponge extract to the level of parasitemia T. evansi in Balb/C mice (Mus musculus L.) and to find out the most optimum Hymeniacidon sp. sponge extract to prevent T. evansi growth. This research has used 40 male Balb/C mice, age 2-3 months, weight ± 23-30 grams. The research subject was divided in to 8 groups (each group contain 5 mice).The classification consists of negative control DMSO, negative control of sponge extract, positive control which is infected by T. evansi and 5 groups treatment T. evansi accompanied with sponge extract given. Sponge extract concentration which was used were 50 mg/kg of BB, 100 mg/kg of BB, 200 mg/kg of BB, 400 mg/kg of BB, and800 mg/kg of BB, respectively. Mice were injected intraperitoneally with 0,2 ml of blood containing 103 of T. evansi. Sponge extract was given orally at 24 hours after T.evansi infection and conducted during 4 days. Then, film blood smear is made, observed by microscope and level of parasitemia T.evansi in blood was calculated.Result of this research indicated that Hymeniacidon sp. kloroform sponge extract concentration variation significantly decrease to the level of parasitemia T. evansi. The most effective concentration is 400 mg/kg of BB with reactivity equal to 98,71% on the fourth days research.